»Gerechter Friede« — »gerechter Krieg«: Christliche Friedensethik vor neuen Herausforderungen - Körtner, Ulrich H. J. (Zeitschrift für Theologie und Kirche, 2003)
During the last decades, the basic attitude of the churches towards peace ethics has been to replace the traditional doctrine of a just war with the doctrine of a just peace. However since 1989 some of the basic prerequisites for policies of peace and security have changed dramatically. An analysis of the most significant positions in regard to peace ethics and of the churches' attitude toward the war in Iraq shows that Christian peace ethics will not be able to do without a modified doctrine of a just war in the future as well. This however must be integrated into a doctrine of a just peace.